The intergenerational transmission of gender: Paternal influences on children's gender attitudes - Cano, Tomás; Hofmeister, Heather (My University, 2022)
Objective This study provides the first systematic longitudinal analysis of the influence of paternal involvement in family life—across childhood and adolescence—on the gender-role attitudes of children by the age of 14 or 15. Background Recent research suggests that, in post-industrial societies, paternal involvement in family life is increasing. Although previous studies of paternal involvement have considered paternal influences on children's cognitive or socio-emotional development, such studies have not yet addressed paternal influences on children's attitudes toward gender. Relatedly, previous studies on the intergenerational transmission of gender attitudes have analyzed maternal influences, but have neglected the significance of paternal influences. This study engages both strands of the research by analyzing the effects of paternal behaviors on children's attitudes toward gender roles. Method Multivariate linear regressions models were estimated on data from the Longitudinal Study of Australian Children (LSAC); a survey with biannual observations over 10 years for 2796 children born between 1999 and 2000. Results Fathers' time spent on childcare during childhood was associated with gender-egalitarian attitudes in children by the age of 14 or 15. The most powerful predictor of children's gender-role attitudes, however, was the amount of time fathers spent on housework during children's adolescence, both absolute and relative to the amount of time mothers spent on housework. Fathers' unpaid labor at home was as relevant for children's gender-role attitudes as mothers' paid labor in the workforce. These results held after controlling for maternal domestic behaviors and for the gender-role attitudes of both parents. Conclusion Father involvement in childcare and housework during childhood and adolescence play an important role in shaping children's gender-egalitarian attitudes.
Journal of Marriage and Family
Keywords: Adolescents and youth; Childhood and child development; Gender